Wykorzystanie metod wyceny w strategicznych i operacyjnych decyzjach podejmowanych przez zakłady ubezpieczeń - Jaworski, Witold (Using valuation methods in strategic and operational decisions made by insurance companies, 2006)
Assessment of actions taken by insurance companies, first of all effectiveness strategy which they put into practice, is more and verified by market mechanism, in which increase of market value of company is most important. This paper presents examples of using valuations methods in making strategic and operational decisions in insurance companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 166-172